2017
DOI: 10.1097/nmd.0000000000000601
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Experiences of the Benefits and Key Elements of a Cognitive Behavioral Intervention Focused on Community Work Outcomes in Persons With Mental Illness

Abstract: New research suggests that group-based cognitive behavioral therapy (CBT) may help improve employment outcomes in persons with mental illness, yet the effects and potential key elements facilitating change in such interventions are unclear. Utilizing a mixed methods approach, this study examined the perspectives of persons with mental illness after participating in a pilot study of the "CBT for Work Success" intervention. Findings demonstrate that participants valued the intervention and perceived that it assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…These findings build upon the results of the developmental pilot of CBTw, in which it was found that persons with SMI engaged in CBTw, were highly satisfied with it, and perceived that it helped them move toward their work goals in the community (Kukla, Strasburger, et al, 2016;Kukla, Strasburger, Salyers, Rattray, & Lysaker, 2017). The current results add to this knowledge by further demonstrating the feasibility of the intervention in a larger sample of people with SMI and by examining preliminary work outcomes.…”
Section: Attrition and Session Attendancesupporting
confidence: 71%
“…These findings build upon the results of the developmental pilot of CBTw, in which it was found that persons with SMI engaged in CBTw, were highly satisfied with it, and perceived that it helped them move toward their work goals in the community (Kukla, Strasburger, et al, 2016;Kukla, Strasburger, Salyers, Rattray, & Lysaker, 2017). The current results add to this knowledge by further demonstrating the feasibility of the intervention in a larger sample of people with SMI and by examining preliminary work outcomes.…”
Section: Attrition and Session Attendancesupporting
confidence: 71%
“…Improvement in recovery attitudes may also link to aspects of the intervention that allow participants to think more deeply about themselves and consider their recovery, in light of personal goals and values. This interpretation is consistent with qualitative results in which an earlier cohort of people with SMI received CBTw and described intervention benefits in their own words, emphasizing the opportunity to think and learn important insights about themselves and clarify their goals and priorities for the future (Kukla, Strasburger, Salyers, Rattray, & Lysaker, 2017).…”
Section: Discussionsupporting
confidence: 85%
“…Although there was no control group in this study, a slightly larger proportion attained employment than in their usual supported employment program alone (43 vs. 33%). Also, participants perceived that the CBT for Work Success program supported them to achieve their work goals (48). Given participants in this study were described as "non-responders" to supported employment alone since they had not gained employment after more than 12 months in the program, this suggests the program may be beneficial to augment supported employment, especially for those facing more barriers to securing employment.…”
Section: Cognitive Behavioral Interventionsmentioning
confidence: 90%